ANALISIS DESAIN GEOMETRIK JALAN RAYA PALIMA-PASANG TENENG KABUPATEN SERANG PROVINSI BANTEN - Nila Prasetyo Artiwi; Euis Amilia; Aripudin Aripudin (LPPM, 2023)
Palima Pasang Teneng Road is a segment that connects Serang Regency and Cilegon City. As a connecting road, this road segment certainly opens up the isolation of the areas it traverses and also opens up opportunities for economic improvement in both regions, apart from that it is traversed by many workers and students. With road conditions that have several horizontal alignments and vertical alignments, the chance of an accident is very likely, so to minimize the occurrence of an accident, a geometric design analysis is carried out on the existing conditions of STA 30+000 to STA 34+000 referring to the 1997 Highways Guidelines on Procedures Intercity Road Geometric Planning No. 038/ TBM/ 1997. Palima-Pasang Teneng road is included in the classification of primary collector road class IIA roads, pavement width 2x3.75 m with rigid pavement. With a design speed of 60 km/h, geometric analysis was carried out on IP-1 (Spiral-Circle-Spiral) bends, IP-6 (Full Circle) bends, and IP-7 (Spiral-Spiral) bends.